Mengungkap Faktor-Faktor Penentu Optimalisasi PBB-P2 di Kabupaten Sumbawa: Pendekatan Kualitatif dan Kebijakan Fiskal - Damayanti, Maharani Putri; Nabila, D. Tialurra Della (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to identify factors that influence the optimization of land building tax (PBB-P2) revenue in Sumbawa Regency, as well as evaluate the effectiveness of fiscal policies implemented by the local government. Using a descriptive qualitative approach, this study examines the dynamics of taxpayer compliance, fiscal policy, and efforts that have been made to increase PBB-P2 revenue. The results show that the low level of taxpayer awareness and compliance, weak policy socialization, and geographical challenges are the main obstacles in optimizing PBB-P2 revenue. On the other hand, efforts to digitize tax services, update data, strengthen coordination between agencies, and plan to provide tax relief are positive steps that have been taken by the local government. This Study recommends the need for fiscal policy innovation based on local needs, increasing tax education to the community, and strengthening the capacity of tax officials to encourage the optimalization og PBB-P2 revenue in a sustainable manner, so that it can support more independent regional development.